Peran Guru Dalam Mengembangkan Kognitif Anak di TK Al-Fadilah Kota Bengkulu - Winda, Elvis; Apriana, Nepi; Dahlan, Alimni (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
This research is motivated by the lack of cognitive development in Al-Fadilah Kindergarten, Bengkulu City. The type of research used is descriptive qualitative. Data collection techniques include observation and interviews. The research subject was 1 person and 2 class B teachers at Al-Fadilah Kindergarten, Bengkulu City. Data analysis was carried out by collecting observation and interview data, reducing, presenting data and drawing research conclusions. The results of research at the Al-Fadilah Kindergarten, Bengkulu City, namely the teacher's role in developing cognitive development in children, including learning about new abilities; generates many relevant ideas or answers and the flow of thoughts is smooth; and the ability to adapt successfully.